MOTIVASI SISWA MEMILIH PROGRAM KEAHLIAN TATA BOGA DI SEKOLAH MENENGAH KEJURUAN - Esti Jannah; Widjiningsih Widjiningsih (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2018)
The objectives of the study were to find out: (1) the levelof students’ motivation in choosing a program of Culinaryexpertise; (2) the intrinsic level of students’ motivation inchoosing a program of Culinary expertise; and (3) the extentof extrinsic motivation of students in choosing a programof Culinary expertise. This research is a descriptive researchtype, the population is students of Program Culinary X classamounting to 127 which is divided into 4 classes. Samplingusing Slovin formula with a significant level of 5% obtainedsample 96 students. Methods of data collection usingquestionnaires. Data analysis techniques use quantitativedescriptive analysis to describe the state of the variable. Theresults showed that (1) the students’ motivation in choosingthe Culinary skill program has a high tendency with relativefrequency of 37.50%. (2) The intrinsic motivation ofstudents in choosing a Culinary skill program has a fairly hightrend with a relative frequency of 37.50%. (3) The extrinsicmotivation of students in choosing a Culinary skill programhas a very high trend with a relative frequency of 39.58%.